Adjustment, Conditionality, and International Financing : Papers Presented at the Seminar on "The Role of the International Monetary Fund in the Adjustment Process" held in Vina del Mar, Chile, April 5-8, 1983. (International Monetary Fund, 1984)
This book, edited by Joaquin Muns, contains papers presented at a seminar in Vina del Mar, Chile, under the sponsorship of the Central Bank of Chile, the Federico Santa Maria University, and the IMF.